What is known about persons with co-occurring problems' experiences with supported housing, recovery, and health promotion? A scoping review - Unn Elisabeth Hammervold; Silje Gytri; Marianne Storm; Torgeir Gilje Lid; Hildegunn Sagvaag (BMC, 2024)
Abstract Background Having a home is the foundation of most people's lives. People with co-occurring substance use and mental health problems may experience challenges in acquiring and keeping housing. Many also have major health challenges. Supported housing is the subject of increasing interest, but there seems to be a lack of studies exploring supported housing's potential for facilitating recovery and health promotion. Therefore, a scoping review was performed to answer our review question: What is known in the literature about the experiences of persons with co-occurring substance use and mental health problems with supported housing, including experiences of recovery and health promotion? Methods Systematic searches were conducted in the Ovid MEDLINE, Embase, PsycInfo, CINAHL, Social Services Abstracts, Web of Science, Scopus, and Oria, and Idunn.no databases. The search terms were derived from the population, concepts, and context. The search for grey literature was conducted in various Norwegian sources. Results Forty studies were included: 7 with quantitative design, 28 with qualitative design and 5 with mixed methods design. The studies were from Canada, Ireland, Norway, Scotland, and the USA. The review identified four themes related to tenants' experiences with supported housing: 1)The importance of a permanent and safe home; 2) Housing's importance for physical health; 3) A shoulder to lean on - the importance of relationships and support; 4) the value of choice and independence. Factors that may influence physical health were poorly represented. Conclusions Long-term housing and safety are prerequisites for recovery for people with co-occurring problems. Programmes such as Housing First and Assertive Community Teams, especially, were experienced to support recovery. Autonomy was valued, including access to individual and respectful support from service providers when needed. Supported housing may be a health-promoting arena, especially in relation to mental health. More attention should be given to how service providers can support tenants to protect their physical health, especially related to nutrition, meals and communal cooking. Further research is needed to tailor optimal services and support for people with co-occurring problems, including balancing support and autonomy with the aim of promoting health and recovery. Peer specialists' contributions to supported housing are scarce and need further development.